2013
DOI: 10.1016/j.trsl.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for the prevention of vein graft disease

Abstract: Ischemic cardiovascular disease remains the leading cause of death worldwide. Despite advances in the medical management of atherosclerosis over the past several decades, many patients require arterial revascularization to reduce mortality and alleviate ischemic symptoms. Technological advancements have led to dramatic increases in the use of percutaneous and endovascular approaches, yet surgical revascularization (bypass surgery) with autologous vein grafts remains a mainstay of therapy for both coronary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 176 publications
0
19
0
Order By: Relevance
“…5,8 Despite evidence that both aspirin and lipid-lowering therapy improve SVG patency 9,10 -as well as widespread implementation of these therapies 7there is no evidence that SVG patency rates have increased since 1968. 11 One study suggested that modern SVG patency rates may be decreasing (*55% by 18 months) and confirmed that loss of SVG patency is associated with poor clinical outcomes. 12 Moreover, SVG stenosis and occlusion are difficult to treat: percutaneous intervention is often unsuccessful, 13 and the morbidity of both percutaneous intervention and redo CABG is high.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…5,8 Despite evidence that both aspirin and lipid-lowering therapy improve SVG patency 9,10 -as well as widespread implementation of these therapies 7there is no evidence that SVG patency rates have increased since 1968. 11 One study suggested that modern SVG patency rates may be decreasing (*55% by 18 months) and confirmed that loss of SVG patency is associated with poor clinical outcomes. 12 Moreover, SVG stenosis and occlusion are difficult to treat: percutaneous intervention is often unsuccessful, 13 and the morbidity of both percutaneous intervention and redo CABG is high.…”
Section: Introductionmentioning
confidence: 95%
“…Gene therapy is an attractive approach for improving SVG patency because it offers the possibility to treat a vein segment (potentially ex vivo) before it is grafted into the arterial circulation. 11,15 Delivery of a durable biological therapy at the time of vein grafting might prevent the processes that cause SVG occlusion (thrombosis, intimal hyperplasia, and accelerated atherosclerosis). 5,16,17 However, because SVG disease (especially atherosclerosis) develops over many years, optimal SVG gene therapy will likely require a vector that can express a therapeutic transgene in blood vessels for years.…”
Section: Introductionmentioning
confidence: 99%
“…Intimal hyperplasia in the vein graft wall is thought to be one of the main causes for such poor long-term findings. As such, many studies have tried to inhibit intimal hyperplasia (5)(6)(7)(8)(9). External stent placement around the vein graft has shown remarkable success in suppressing intimal hyperplasia (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…[58][59][60] Whatever the vector, there are two methods by which gene therapy can be carried out: 1. in vivo gene therapy, in which the vector is injected into the body and has to find its way to the target tissue 2. ex vivo in which a sample of tissue is taken from the patient, treated with the vector and then replaced. 61 Currently active trials of gene therapy are going on over such varied diseases cystic fibrosis, vein graft rejection, psychiatric d i sorders, inner ear developmental anomalies, brain tumors, mitochondrial genetic diseases. [61][62][63][64][65][66][67][68][69] The use of viruses to deliver genes has shown risks to human health, making trials with these viruses controversial.…”
Section: Transgenic Animalsmentioning
confidence: 99%
“…61 Currently active trials of gene therapy are going on over such varied diseases cystic fibrosis, vein graft rejection, psychiatric d i sorders, inner ear developmental anomalies, brain tumors, mitochondrial genetic diseases. [61][62][63][64][65][66][67][68][69] The use of viruses to deliver genes has shown risks to human health, making trials with these viruses controversial. Another method involves the use of liposomes, hollow membranous spheres which encapsulate the gene.…”
Section: Transgenic Animalsmentioning
confidence: 99%